Using webquests in a museum-based multiliteracies dynamic learning intervention: ubiquitous learning made possible? - Souleles, Nicos; Savva, Stefania (My University, 2013)
Today’s emerging technological achievements seem to be moving towards the realization of ubiquitous learning as described by Weiser (1991). Nevertheless, ubiquitous learning is not preconceived or a priori; the number of possibilities offered by such learning can only happen “if breakthrough strategies and practices are implemented that reconceptualize the content, processes and human relationships of teaching and learning” (Cope and Kalantzis, 2008:582). Bearing the previous in mind, the aim of this paper is to report on the findings from a doctoral thesis on pupils’ learning experiences of and through museum-based multiliteracies. Drawing from the literature, analysis and evaluation of the qualitative research methodology this paper addresses how engagement with an online educational tool such as webquests impacts upon pupils’ multiliteracies learning experiences, and what kind of multiliteracies pedagogy approach can support ubiquitous learning. To facilitate understanding a learning framework developed for the purposes of an educational intervention, the Museum Multiliteracies Practice (MMP) is presented in brief. Following this, the findings of the intervention are discussed in the context of the case study undertaken with a group of primary aged students to determine the extent to which the intrinsic characteristics of ubiquitous learning could be served by the affordances of the webquest method and multiliteracies pedagogy.
Keywords: Learning framework; Webquests; Multiliteracies pedagogy; Ubiquitous learning; Virtual museum